Designing and implementing a practical prehospital emergency trauma care curriculum for lay first responders in Guatemala. Issue 1 (2nd April 2020) - Delaney, Peter G; Figueroa, Jose A; Eisner, Zachary J; Hernandez Andrade, Rudy Erik; Karmakar, Monita; Scott, John W; Raghavendran, Krishnan
Abstract : Background: Injury disproportionately affects low-income and middle-income countries, yet robust emergency medical services are often lacking to effectively address the prehospital injury burden. A half-day prehospital emergency trauma care curriculum was designed for first responders and piloted in the Sacatepéquez, Chimaltenango, and Escuintla departments in Guatemala. Methods: Three hundred and fifty-four law enforcement personnel, firefighters, and civilians volunteered to participate in a 5-hour emergency care course teaching scene safety, triage, airway management, cardiopulmonary resuscitation, fracture management, and victim transport. A validated 26-question pretest/post-test study instrument was contextually adapted and used to measure overall test performance, the primary study outcome, as well as test performance stratified by occupation, the secondary study outcome. Pretest/post-test score distributions were compared using a Wilcoxon signed-rank test. For test evaluation, knowledge acquisition on a by-question and by-category basis was examined using McNemar's χ² test, whereas item difficulty indices used frequency-of-distribution tests and item discrimination indices used point biserial correlation. Results: Two hundred and eighty-seven participants qualified for inclusion. Participant mean pretest versus post-test scores improved 24 percentage points after course completion (43% vs 68%, p<0.001). Cronbach's alpha yielded values of 0.86 (pretest) and 0.94 (post-test), suggesting testing instrument reliability. Between-group analyses demonstrated law enforcement and civilian participants improved more than firefighters (p<0.001). Performance on 23 of 26 questions improved significantly. All test questions except one showed an increase in their PPDI. Discussion: A 1-day, contextually adapted, 5-hour course targeting laypeople demonstrates significant improvements in emergency care knowledge. Future investigations of similar curricula should be trialed in alternate low-resource settings with increased civilian participation to evaluate efficacy and replicability as adequate substitutes for longer courses. This study suggests future courses teaching emergency care for lay first responders may be reduced to 5 hours duration. Level of evidence: Level II.